Mengukur Efektivitas Program Pasca Pelatihan Baru: Studi pada Model Reformer DIKLAT PIM: Measuring the Post-Training Effectiveness of New Training Programs: A Study on DIKLAT PIM Reformer Model - Ruslan Kamis; Abdullah W Jabid; Adnan Rajak; Johan Fahri (Society, 2022)
Studies have shown indications of performance improvement due to a training program. In the public sector, this program is highly expected to impact how the officers can demonstrate their capacity to perform their duties well. This program includes a new leadership education and training program called DIKTLAT PIM Model Reformer. This study was aimed at contextually examining the effectiveness of this new model of a training program. This study demonstrated how the basic rule (Regulation of the Head of State Administration Agency Number 13 of 2013 concerning Guidelines for Organizing Level IV Leadership Education and Training) on post-training evaluation was conducted. This current study’s novelty lies in its use of the grounded theory method as an evaluation approach for post-training effectiveness. This current study used the Grounded Theory Method (GTM) and focused on alumni training at the Municipality of Tidore Islands, North Maluku, Indonesia. The results indicated several aspects identified and defined by the alumni concerning the new training program model. The aspects include effectiveness and efficiency improvement, competency measures, leader morality and professionalism, teamwork, source financing, and performance evaluation. This current study enabled its basic regulation on measuring the effectiveness of the training program—DIKTLAT PIM Model Reformer. Future studies are also proposed to overcome this study’s weakness.